PHYTOCHEMICAL SCREENING, PROXIMATE ANALYSIS AND MINERAL COMPOSITION OF UNRIPE Citrus reticulata PEELS (FUDMA JOURNAL OF SCIENCES, 2023)
A study was conducted to know the nutritive value of unripe Citrus reticulata peels. The standard procedures were followed for phytochemical screening, proximate composition and mineral analysis. Proximate analysis was conducted to determine the key elements in the form of water, ash, carbohydrates, proteins and fats. Thecalcium (Ca), magnesium (Mg), iron (Fe), zinc (Zn) and manganese (Mn) were determined by Atomic Absorption Spectrophotometer, sodium (Na) and potassium (K) by Flame Photometer and phosphorus (P) by Spectrophotometer. The result revealed that the tested unripe Citrus reticulata peels contained alkaloids, flavonoids, phenols, saponins, steroids, tannins, xanthoprotein, cardiac glycosides, phlobatannins, Coumarins and no oxalate. The results also revealed that unripe Citrus reticulata peels contained moisture (4.40±0.15%), ash (8.87±0.29%), crude fat (19.93±0.81%), crude fiber (3.35±0.10%), crude protein (13.42±0.58%) and carbohydrate (50.03±0.84%). While the mineral  determination gave the data that unripe Citrus reticulata peels contained Na (23.78±0.17mg/100g), K (18.73±0.01mg/100g), Ca (14.23±0.02mg/100g), Mg (371.90±0.82mg/100g), P (24.52±0.72mg/100g), Fe (203.72±0.18mg/100g), Zn (61.58±0.58mg/100g) and Mn (12.27±0.02mg/100g). And also the highest amount of carbohydrate and magnesium. The results suggest that the unripe Citrus reticulata peels is a source of bioactive compounds, nutrients and essential minerals which may make it useful for therapeutic uses, in nutrition and has a great potential in complementing minerals deficiencies.
Keywords: Phytochemicals, proximate analysis, minerals, unripe Citrus reticulatapeels